Controlling the optical and structural properties of ZnS–AgInS2 nanocrystals by using a photo-induced process - Yatsui, Takashi; Morigaki, Fumihiro; Kawazoe, Tadashi (Beilstein Journal of Nanotechnology, 2014)
ZnS–AgInS2 (ZAIS) solid-solution nanocrystals are promising materials for nanophotonic devices in the visible region because of their low toxicity and good emission properties. We developed a technique of photo-induced synthesis to control the size and composition of the ZAIS nanocrystals. This method successfully decreased the defect levels, as well as the size and size variation of ZAIS nanocrystals by controlling the excitation wavelength during synthesis. Detailed analysis of transmission electron microscope images confirmed that the photo-induced synthesis yielded a high crystallinity of the ZAIS nanocrystals with small variations in size and content.
Keywords: low toxicity; self-assembly; visible-light-emitting nanocrystals; ZnS–AgInS2 (ZAIS)

(untitled) - Kirchain, R.; Kimerling, L. (Nat. Photonics, 2007)

(untitled) - Gramotnev, D. K.; Bozhevolnyi, S. I. (Nat. Photonics, 2014)

(untitled) - Kawazoe, T.; Kobayashi, K.; Lim, J.; Narita, Y.; Ohtsu, M. (Phys. Rev. Lett., 2002)

(untitled) - Yatsui, T.; Jeong, H.; Ohtsu, M. (Appl. Phys. B, 2008)

(untitled) - Yatsui, T.; Sangu, S.; Kawazoe, T.; Ohtsu, M.; An, S. J.; Yoo, J.; Yi, G.-C. (Appl. Phys. Lett., 2007)

(untitled) - Yatsui, T.; Nomura, W.; Mano, T.; Miyazaki, H. T.; Sakoda, K.; Kawazoe, T.; Ohtsu, M. (Appl. Phys. A, 2014)

(untitled) - Kawazoe, T.; Ohtsu, M.; Aso, S.; Sawado, Y.; Hosoda, Y.; Yoshizawa, K.; Akahane, K.; Yamamoto, N.; Naruse, M. (Appl. Phys. B, 2011)

(untitled) - Mukai, K.; Abe, S.; Sumi, H. (J. Phys. Chem. B, 1999)

(untitled) - Ohtsu, M.; Kawazoe, T.; Yatsui, T.; Naruse, M. (IEEE J. Sel. Top. Quantum Electron., 2008)

(untitled) - Peng, X.; Manna, L.; Yang, W.; Wickham, J.; Scher, E.; Kadavanich, A.; Alivisatos, A. P. (Nature, 2000)

(untitled) - Shirasaki, Y.; Supran, G. J.; Bawendi, M. G.; Bulović, V. (Nat. Photonics, 2013)

(untitled) - Mashford, B. S.; Stevenson, M.; Popovic, Z.; Hamilton, C.; Zhou, Z.; Breen, C.; Steckel, J.; Bulovic, V.; Bawendi, M.; Coe-Sullivan, S.; Kazlas, P. T. (Nat. Photonics, 2013)

(untitled) - Torimoto, T.; Adachi, T.; Okazaki, K.-i.; Sakuraoka, M.; Shibayama, T.; Ohtani, B.; Kudo, A.; Kuwabata, S. (J. Am. Chem. Soc., 2007)

(untitled) - Torimoto, T.; Murakami, S.-y.; Sakuraoka, M.; Iwasaki, K.; Okazaki, K.-i.; Shibayama, T.; Ohtani, B. (J. Phys. Chem. B, 2006)

(untitled) - Xia, F.; Sekaric, L.; Vlasov, Y. (Nat. Photonics, 2007)

(untitled) - Liu, Y.; Morishima, T.; Yatsui, T.; Kawazoe, T.; Ohtsu, M. (Nanotechnology, 2011)

(untitled) - Liu, Y.; Yatsui, T.; Ohtsu, M. (Appl. Phys. B, 2012)

(untitled) - Koyama, H.; Koshida, N. (J. Appl. Phys., 1993)

(untitled) - Deng, M.; Shen, S.; Wang, X.; Zhang, Y.; Xu, H.; Zhang, T.; Wang, Q. (CrystEngComm, 2013)

(untitled) - Gayou, V. L.; Salazar Hernández, B.; Delgado Macuil, R.; Zavala, G.; Santiago, P.; Oliva, A. I. (J. Nano Res., 2010)